BIM AND GIS INTEGRATED UTILITY SUPPLY STATION LOCATION OPTIMIZATION AND POSSIBILITIES - Rabia M P, Rahla; Sathish Kumar D (Journal of Applied Engineering Science, 2022)
Optimal planning of utility supply station location is an integral part of infrastructural projects. In general, this is a multi-objective optimization process by considering engineering, financial and geographical constraints. A shift from conventional 2D-CAD, manual quantification and design application-based approach to Building Information Modelling (BIM)-Geographic Information System (GIS) integrated approach is found to be suitable for minimizing optimal planning time, cost and increasing automation. In this paper, an Autodesk Revit add-in tool is proposed aimed at integrating BIM and GIS for Genetic Algorithm (GA) based utility supply station location optimization and to assess the possibilities of this integration. From the case study it is observed that up to 90% of cost saving can be accomplished by this proposed approach. It is found that compared to the traditional multi-software approach with manual data transfer, this integration can be utilized for multi-stage optimization and is suitable for automating heterogenous data integration with increased accuracy. The platform in which the add-in tool is developed for the utility network can be at either BIM or GIS and this selection is influenced by the availability and ease of data retrieval from the respective semantic information system and the level of automation that is to be accomplished. Standardised BIM-based modelling combined with concepts like artificial intelligence and image processing techniques can be promising for attaining desired results in industrial applications.